TINGKAT PENGETAHUAN SISWA TENTANG GIZI SEIMBANG TERHADAP PERTUMBUHAN FISIK DI SMAN 1 MERANGIN - Yofi Ariandsyah; Sukendro; Bangkit Yudho Prabowo; Fitri Diana; Anggrawan Janur Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The level of students’ knowledge regarding balanced nutrition and its relationship to physical growth at SMA Negeri 1 Merangin has not been widely studied. This research aimed to determine the level of knowledge of grade X, XI, and XII students about balanced nutrition in relation to physical growth.This study employed a descriptive quantitative method with a cross-sectional design. The population consisted of 981 students, with a sample of 76 students selected using proportionate stratified random sampling. Data were collected through a 40-item questionnaire adapted from the Adolescent Nutrition Knowledge Questionnaire (ANKQ) and the Indonesian Balanced Nutrition Guidelines, as well as measurements of body weight and height to determine Body Mass Index (BMI). Data were analyzed using descriptive statistics. The results showed that the average knowledge score was 35.84 out of 40 (89.6%). Most students were categorized as having very good knowledge (80.3%), followed by good (17.1%), sufficient (1.3%), and poor (1.3%). All dimensions of balanced nutrition knowledge were classified as very good. However, BMI results indicated that only 51.3% of students had normal nutritional status, while 27.6% were underweight, 17.1% were overweight, and 3.9% were obese. These findings suggest that high nutritional knowledge does not necessarily correspond to ideal nutritional status, as it may also be influenced by dietary habits, food accessibility, and socioeconomic factors.